PENGARUH PENDIDIKAN KESEHATAN TENTANG HAND HYGIENE TERHADAP PELAKSANAAN HAND HYGIENE SEBELUM MAKAN PADA SANTRIWAN PONDOK PESANTREN - S.Kep.Ns.,M.Kes, HeriTriwibowo,; Frilasari, SST.,M.Kes, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Hand hygiene behavior is less precise santriwan still found in the boarding school, there is no evidence that health education can influence behavior in washing hands and becomes a habit that is applied in everyday life. The purpose of this study was to determine health education effect of hand hygiene on the implementation of hand hygiene at the boarding school santriwan Fatchul Ulum, Pacet, Mojokerto. The study design used is pre-experimental design with one-group pre-post test design. The samples in this study using systematic random sampling technique. The population in this study were 116 people, there are 30 people who responded. Variables measured by the implementation of hand hygiene observation twice. Based on the Wilcoxon signed rank test obtained (pvalue = 0.014). which mean that there are effect of health education on hand hygiene for the implementation of hand hygiene santriwan boarding Fatchul Ulum, Pacet, Mojokerto. This is because the health education can provide a stimulus that causes increase in the respondents knowledge so that it can affect behavior change.Keywords: Hand hygiene, Health Education, Behavior.